Legitimacy of government in jurisprudence and law - Bahadur, Mohammadullah (Journal of Social Sciences - Kabul University, 2023)
Legitimacy of the government is that the rulers come to power through legal means and their actions and activities are carried out according to the law. The realm of legitimacy is a broad concept that includes political, legal and religious legitimacy in the legal system. A government that is beyond the law and sharia lacks legitimacy. The government, ministries and government institutions gain legitimacy and authority by implementing laws, providing public services, providing basic and political rights of the people, granting material and spiritual privileges to all government officials and supporting freedoms in the society.The purpose of the article is to explain the concept, types and foundations of the legitimacy of government in jurisprudence and law. The present article is a descriptive research type and various sources such as books and articles are used in its preparation and arrangement. The findings of this article show that governments should have different levels of legitimacy from the establishment stage to the exercise of power or authority. From the point of view of Islam, governments are legitimate by applying the rules of Sharia and the law of government, and otherwise, the Islamic government's legal and Shariah legitimacy will be questioned.